`g(theta) = e^(theta) (tan(theta) - theta)` Differentiate.

Textbook Question

Chapter 3, 3.3 - Problem 6 - Calculus: Early Transcendentals (7th Edition, James Stewart).
See all solutions for this textbook.

1 Answer | Add Yours

balajia's profile pic

balajia | College Teacher | (Level 1) eNoter

Posted on

`g(theta)=e^(theta)tantheta-thetae^(theta)`

`g'(theta)=e^(theta)tantheta+e^(theta)sec^2theta-(thetae^(theta)+e^(theta))`

`g'(theta)=e^(theta)(tantheta+sec^2theta-theta-1)`

We’ve answered 318,911 questions. We can answer yours, too.

Ask a question